Pengaruh Pengalaman, Disiplin, dan Motivasi Intrinsik Pada Prestasi Kerja Karyawan PT Adi Satria Abadi Yogyakarta - Ignatius Soni Kurniawan; Atik Setyo Rini (Universitas Muhammadiyah Jember, 2022)
This study aims to determine the effect of work experience, work discipline, and intrinsic motivation on employee performance. The research population is 214 employees of PT Adi Satria Abadi Yogyakarta. The sampling technique used was accidental sampling. Data were collected through a survey of employees using a questionnaire instrument. Data were analyzed using multiple linear regression test. Research findings state that work experience, work discipline, and intrinsic motivation have a positive and significant effect on employee performance.